2010
DOI: 10.1073/pnas.1000704107
|View full text |Cite
|
Sign up to set email alerts
|

Imprints of the genetic code in the ribosome

Abstract: The establishment of the genetic code remains elusive nearly five decades after the code was elucidated. The stereochemical hypothesis postulates that the code developed from interactions between nucleotides and amino acids, yet supporting evidence in a biological context is lacking. We show here that anticodons are selectively enriched near their respective amino acids in the ribosome, and that such enrichment is significantly correlated with the canonical code over random codes. Ribosomal anticodon-amino aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
94
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(101 citation statements)
references
References 35 publications
7
94
0
Order By: Relevance
“…Johnson and Wang (2010), looking for relics of the underlying force driving the evolution of the genetic code, found that it is the anticodonamino acid association, but not the codon-amino acid association that correlates with the genetic code. This conclusion advances the stereochemical hypothesis by pinpointing anticodon-amino acid interaction as the potential drive for code formation.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Johnson and Wang (2010), looking for relics of the underlying force driving the evolution of the genetic code, found that it is the anticodonamino acid association, but not the codon-amino acid association that correlates with the genetic code. This conclusion advances the stereochemical hypothesis by pinpointing anticodon-amino acid interaction as the potential drive for code formation.…”
Section: Discussionmentioning
confidence: 98%
“…Not only the tRNA or the aaRS have been implicated in the evolution of the SGC but also the ribosome seems to have imprints from an early evolution stage of life to establish the translation of the genetic code before LUCA (Fox and Naik 2004;Johnson and Wang 2010). Johnson and Wang (2010), looking for relics of the underlying force driving the evolution of the genetic code, found that it is the anticodonamino acid association, but not the codon-amino acid association that correlates with the genetic code.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though murine CD8 − and CD8 + DC subsets expressed IDO protein in response to IFNγ treatment, only CD8 + DCs produced kynurenine, indicating IDO enzyme activity (Fallarino et al, 2002). Systemic treatments with soluble CTLA4 (CTLA4-Ig) and relatively high doses of TLR9 ligands (CpGs) were also able to induce CD8 + DCs to express functional IDO by ligating B7 or TLR9 molecules and inducing IDO via IFNα signaling in a rare, but distinctive subset of splenic CD19 + DCs co-expressing CD8, the plasmacytoid DC (pDC) marker B220, as well as CD19 and other B cell markers (Grohmann et al, 2002; Mellor et al, 2003, 2005;Baban et al, 2005;Johnson et al, 2010). In humans, monocyte-derived DCs competent to express IDO in response to IFNγ were a discrete subset of DCs expressing the chemokine receptor CCR6 and the pDC marker CD123 (Munn et al, 2002), and human DCs expressing IDO in response to CpGs also exhibited pDC attributes (Chen et al, 2008).…”
Section: Ido-competent Dcsmentioning
confidence: 99%
“…For this reason pDCs may be critical mediators of hyper-immune syndromes since they are major (but not exclusive) sources of type I IFNs, especially in response to pathogen-associated molecular patterns (PAMPs) such as TLRs. It may be pertinent that IDO-competent DCs in humans and mice exhibit attributes that overlap with those of conventional pDCs, as well as other lymphoid and myeloid subsets (Munn et al, 2002; Chen et al, 2008;Johnson et al, 2010). Nevertheless, the role of IFNs, and the cells that produce IFNs, in hyper-immune syndromes is far from clear as IFNs mediate multiple downstream effects that encompass immune stimulatory and immune regulatory pathways.…”
Section: Manipulating Ido To Create or Destroy Immune Privilegementioning
confidence: 99%